Development of Live Working Robot for Replacing Insulators on Power Transmission Lines. Issue 2 (February 2019) - Liu, Lanlan; Yan, Yu; Zhou, Zhanfan; Guo, Hao; Li, Wen; Cao, Zenghui
Abstract: The paper presented the independently developed live working robot for replacing insulators on 110-220kV power transmission lines. By control system and simulating the manual equipotential live working process of replacing insulators, the robot is designed to be composed of a non-obstacle-surmounting platform, a control platform and a ground base station, among which the non-obstacle-surmounting platform mainly consists of the robot body, two robot arms, two robot hands, and two end-effectors, the control platform consists of a motion control system, a communication system, an image capture system and a power management system, and the ground base station consists of an industrial PC equipped with a wireless network interface card and a 3G network interface card. Moreover, the robot is designed to be protected against electromagnetic interference. The robot presented in this paper is the first of its kind in China.